Short stories for students. presenting analysis, context, and criticism on commonly studied short stories - Constantakis, Sara (Gale virtual reference library, 2010)
Provides critical overviews of short stories from all cultures and time periods. Includes discussions of plot, characters, themes and structure as well as the story's cultural and historical significance.